Rise of dinosaurs reveals major body-size transitions are driven by passive processes of trait evolution - Sookias, Roland B. (The Royal Society, 2012)
A major macroevolutionary question concerns how long-term patterns of body-size evolution are underpinned by smaller scale processes along lineages. One outstanding long-term transition is the replacement of basal therapsids (stem-group mammals) by archosauromorphs, including dinosaurs, as the dominant large-bodied terrestrial fauna during the Triassic (approx. 252–201 million years ago). This landmark event preceded more than 150 million years of archosauromorph dominance. We analyse a new body-size dataset of more than 400 therapsid and archosauromorph species spanning the Late Permian–Middle Jurassic. Maximum-likelihood analyses indicate that Cope's rule (an active within-lineage trend of body-size increase) is extremely rare, despite conspicuous patterns of body-size turnover, and contrary to proposals that Cope's rule is central to vertebrate evolution. Instead, passive processes predominate in taxonomically and ecomorphologically more inclusive clades, with stasis common in less inclusive clades. Body-size limits are clade-dependent, suggesting intrinsic, biological factors are more important than the external environment. This clade-dependence is exemplified by maximum size of Middle–early Late Triassic archosauromorph predators exceeding that of contemporary herbivores, breaking a widely-accepted ‘rule’ that herbivore maximum size greatly exceeds carnivore maximum size. Archosauromorph and dinosaur dominance occurred via opportunistic replacement of therapsids following extinction, but were facilitated by higher archosauromorph growth rates.